2008
DOI: 10.1007/s12272-001-1174-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidative and inhibitory activities on nitric oxide (NO) and prostaglandin E2 (COX-2) production of flavonoids from seeds of Prunus tomentosa Thunberg

Abstract: Chemical investigation of the 80% Me(2)CO extract from the seeds of Prunus tomentosa led to the isolation and identification of six flavonoids: kaempferol (1), kaempferol 3-O-alpha-L-rhamnopyranoside (2; afzelin), kaempferol 3-O-beta-D-(6-acetyl)-glucopyranosyl(1-->4)-alpha-L-rhamnopyranoside (3; multiflorin A), kaempferol 3-O-beta-D-glucopyranosyl(1-->4)-alpha-L-rhamnopyranoside (4; multiflorin B), quercetin 3-O-alpha-L-rhamnopyranoside (5; quercitrin), and quercetin 3-O-beta-D-glucopyranosyl (1-->4)-alpha-L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 12 publications
0
46
0
1
Order By: Relevance
“…Afzelin is a well-known flavonoid with anti-inflammatory, antitumor, and antibacterial activities [1,12,18]. We demonstrated here that afzelin possesses melanogenic activity and that it mediates its effects by activating p38 MAPK.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Afzelin is a well-known flavonoid with anti-inflammatory, antitumor, and antibacterial activities [1,12,18]. We demonstrated here that afzelin possesses melanogenic activity and that it mediates its effects by activating p38 MAPK.…”
Section: Discussionmentioning
confidence: 62%
“…The flavonoid afzelin (Kaempferol 3 -O-a-L-rhamnopyranoside) inhibits lipid peroxidation and cyclooxygenase (COX)-1 and COX-2 [12]. The structure of this compound is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that AA and other natural compounds are capable of scavenging nitrite (Kim et al, 2008). Dose-dependent AA-2βG and AA nitrite scavenging activity was observed at low pH (pH 3.0) (Fig.…”
Section: − ) Scavenging Activitymentioning
confidence: 86%
“…The AA or AA-2βG nitrite scavenging capacity was determined by colorimetry, as described previously (Kim et al, 2008), and the absorbance was measured at 538 nm. The percentage of nitrite scavenging was calculated using the following equation: NO 2 − scavenging efficiency (%) = (A 0 − A S )/A 0 × 100, where A 0 and A S represent the control or sample (AA or AA-2βG) absorbance, respectively.…”
Section: ) Scavenging Assaymentioning
confidence: 99%
“…Flavonoids are the well studied class of polyphenols as COX-2 inhibitors. Kaempferol and its derivatives isolated from seeds of Prunus tomentosa exhibited inhibitory activities on nitric oxide (NO) and prostaglandin E 2 (COX-2) production [52]. Kaempferol and quercetin exhibited anti-inflammatory activities by inhibiting iNOS and COX-2 protein levels in cultured human umbilical vein endothelial cells [53].…”
Section: Discussionmentioning
confidence: 99%